INVESTIGATING THE PRODUCTION OF EXTRACELLULAR ENZYMES OF VIBRIO PARAHAEMOLYTICUS STRAINS ISOLATED IN VIETNAM - Vu, Ngo Nguyen; Thu Hien, Pham Thi; Minh Tien, Le Nguyen; Phuc Chau, Do Ngoc; Tung, Hoang; Thu Hoai, Nguyen Thi (Vietnam Journal of Biotechnology, 2018)
Acute Hepatopancreatic Necrosis Disease (AHPND) is a widespread disease targeting cultured shrimps, which results in heavy losses in many regions around the world including Vietnam. The causative agent of the disease is Vibrio paraheamolyticus which is a Gram-negative bacterium present ubiquitously in marine environment. However, this normal floral organism once acquired a plasmid containing Pir- toxin encoding gene (AHPND plasmid) can transform into a highly toxic strain (AHPND strain) with the ability to kill a large number of cultured shrimps in a short period. To understand more on the virulence of V. parahaemolyticus, 17 different V. parahaemolyticus isolates collected from different locations in Southern Vietnam have been analyzed for the presence of AHPND plasmid using PCR method and their extracellular enzyme profile using agar- based method. Seven enzymes which are known to be important virulence factors of the bacterium were studied including caseinase, gelatinase, lecithinase, hemolysin, elastase, lipase and chitinase. Results showed that among 17 studied isolates, six were detected to have AHPND plasmid. Enzymatic activity was observed for caseinase, gelatinase and lecithinase while undetectable for others. The ability to produce these three enzymes varied among different V. parahaemolyticus isolates. Lecithinase appeared in all isolates while the presence of caseinase and gelatinase varied. This indicated that lecithinase seems to be core enzyme of V. paraheamolyticus and the extracellular enzymes do not correlate with the presence of AHPND plasmid. In conclusion, our data suggested that the virulence of Vibrio parahaemolyticus mostly depends on the presence of AHPND plasmid other than extracellular enzymes.